2018
DOI: 10.1021/acs.iecr.8b01088
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High Purity Lactide Using a High-Boiling-Point Alcohol Immobilization Method

Abstract: During the lactide producing process, volatile impurities, such as lactic acid and its dimer, are simultaneously distilled out with lactide. To remove these impurities, many post-treatments were needed. Herein, we present a novel approach to obtain high purity lactide by adding high-boiling-point alcohols to immobilize these volatile impurities. A series of high-boiling-point alcohols were screened and pentaerythritol was found to be the best immobilization reagent. When the molar ratio of lactic acid’s carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…5,11−14 However, the yields of lactide when using such catalysts are often below 80% because the catalysts can also catalyze side reactions. 15,16 For instance, according to Jiang et al, 15 the yield of lactide was 77.5% when using SnCl 2 at a catalyst loading of 0.1 mol % relative to OPLA. In addition, Cao et al 16 used SnO as a catalyst for lactide production and only achieved a 73% yield with a catalyst loading of 0.4 wt %.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,11−14 However, the yields of lactide when using such catalysts are often below 80% because the catalysts can also catalyze side reactions. 15,16 For instance, according to Jiang et al, 15 the yield of lactide was 77.5% when using SnCl 2 at a catalyst loading of 0.1 mol % relative to OPLA. In addition, Cao et al 16 used SnO as a catalyst for lactide production and only achieved a 73% yield with a catalyst loading of 0.4 wt %.…”
Section: ■ Introductionmentioning
confidence: 99%
“…15,16 For instance, according to Jiang et al, 15 the yield of lactide was 77.5% when using SnCl 2 at a catalyst loading of 0.1 mol % relative to OPLA. In addition, Cao et al 16 used SnO as a catalyst for lactide production and only achieved a 73% yield with a catalyst loading of 0.4 wt %. Some other metal compounds have also been used as catalysts; however, their catalytic performances are also poor due to the same problems as mentioned above.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of different catalytic systems have been proposed since, which makes it possible to obtain lactide in high yield, selectivity, and optical purity [103,104,155,156]. Additionally, there appeared new versions of its synthesis using microwave radiation [157][158][159], various solvents [160], oligomer modifiers (e.g., polyhydric alcohols) [161][162][163], etc. Some approaches are similar to methods for glycolide obtainment.…”
Section: Classic Approach To the Synthesis Of Lactide By Depolymerization Of Lactic Acid Oligomers And The Main Approaches Of Process Modmentioning
confidence: 99%
“…Further studies have shown that polyhydric high-boiling alcohols affect the depolymerization of oligomers, and an increase in the number of hydroxyl end groups is not the sole reason for that. Wang et al found that when oligomers are modified with polyhydric alcohols with further depolymerization, the acid residue and its lowmolecular weight oligomers are bound (immobilized) as esters that have a higher boiling point; therefore, they are not distilled with lactide during oligomers depolymerization and do not cause contamination (Table 8, entry 22) [163]. The depolymerization of oligomers modified with pentaerythritol shows a crude lactide yield of 93% and purity of L-lactide after purification approximating 99%.…”
Section: Depolymerization Of Modified Lactic Acid Oligomersmentioning
confidence: 99%